Current Overview of Metal Nanoparticles’ Synthesis, Characterization, and Biomedical Applications, with a Focus on Silver and Gold Nanoparticles - Ana Flavia Burlec; Andreia Corciova; Monica Boev; Denisa Batir-Marin; Cornelia Mircea; Oana Cioanca; Gabriela Danila; Marius Danila; Anca Florentina Bucur; Monica Hancianu (Pharmaceuticals, 2023)
Metal nanoparticles (NPs) have garnered considerable attention, due to their unique physicochemical properties, that render them promising candidates for various applications in medicine and industry. This article offers a comprehensive overview of the most recent advancements in the manufacturing, characterization, and biomedical utilization of metal NPs, with a primary focus on silver and gold NPs. Their potential as effective anticancer, anti-inflammatory, and antimicrobial agents, drug delivery systems, and imaging agents in the diagnosis and treatment of a variety of disorders is reviewed. Moreover, their translation to therapeutic settings, and the issue of their inclusion in clinical trials, are assessed in light of over 30 clinical investigations that concentrate on administering either silver or gold NPs in conditions ranging from nosocomial infections to different types of cancers. This paper aims not only to examine the biocompatibility of nanomaterials but also to emphasize potential challenges that may limit their safe integration into healthcare practices. More than 100 nanomedicines are currently on the market, which justifies ongoing study into the use of nanomaterials in medicine. Overall, the present review aims to highlight the potential of silver and gold NPs as innovative and effective therapeutics in the field of biomedicine, citing some of their most relevant current applications.